Scalable high performance computing in wide area network - Hassani, R.; Luksch, P. (2012 International Conference on High Performance Computing and Simulation, 2012)
Many parallel applications in High Performance Computing have to communicate via wide area network (WAN), e.g., in a grid or cloud environment that spans multiple sites. Communication across WAN links slows down the application due to high latency and low bandwidth. Much of this overhead is due to the current implementations of the MPI (Message Passing Interface) standard. My project aims at improving WAN performance of MPI. Virtually most of today's wide area MPI implementations rely on the TCP/IP protocol. I propose to replace it by an innovative concurrent multipath communication method (CMC-SCTP) and integrate it with Open MPI project, which will increase bandwidth and enhance fault resilience within the MPI protocol stack in WAN environment. I plan to make my research results available to the community within the scope of the Open MPI project.